AUDIT COMMITTEE MODERATION IN THE NEXUS BETWEEN SUSTAINABILITY REPORTING AND TAX AVOIDANCE: EVIDENCE FROM INDONESIAN MULTINATIONAL FIRMS - Ismawati, Erlina; Novita, Santi (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study investigates the moderating role of the Audit Committee in the relationship between sustainability reporting and tax avoidance among Indonesian multinational corporations listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Panel data were collected from annual reports, Osiris, and Bloomberg databases, with firm selection based on the availability and completeness of financial and ESG disclosures. The final sample comprises 66 multinational firms, yielding 277 firm-year observations, analyzed using panel regression with robust standard errors. The empirical findings reveal that higher levels of sustainability disclosure are significantly associated with greater tax avoidance, suggesting the presence of “sustainability washing,” where reporting serves symbolic rather than substantive purposes. Contrary to expectations, the Audit Committee does not significantly moderate this relationship. Only firm age exhibits a significant negative association with tax avoidance among the control variables, indicating that more mature firms prioritize long-term legitimacy over short-term tax benefits. Beyond its practical implications for regulators and policymakers, such as the Financial Services Authority (OJK) and the Directorate General of Taxes (DJP), who are urged to strengthen oversight and integrate tax accountability within ESG frameworks, this study also contributes theoretically to the ESG tax nexus literature. It extends legitimacy theory by demonstrating that sustainability disclosure, typically framed as legitimacy-enhancing, may paradoxically facilitate opportunistic strategies like tax avoidance in emerging market contexts. This duality underscores the importance of governance effectiveness in ensuring sustainability reporting translates into genuine fiscal transparency.